The Financial and Tax Law and its Relationship with Private Law - Parmenion Espeche, Sebastián (2014)
The purpose of this paper is to glimpse as the Tax Law is inserted in the unit of general law, being important for understanding the knowledge of public and private law in general.In the second part of the paper, the author analyzes how private law applies to the financial subsidiary way through forwarding making the tax law itself or by express provision of the civil. He emphasizes in this introduction as dogmatic construction of the tax liability, originated and rationale in civil liability.Finally the author explains how general principles of law necessarily apply to financial law. Thus, the principles of good faith, breach of law, and the doctrine of estoppel, are universal principles applicable to every right and inexcusably financial and tax law.